Waste as a Source of Fuel and Developments in Hydrogen Storage: Applied Cases in Spain and Their Future Potential - Pous de la Flor, Juan; Martínez-Hernando, María-Pilar; Paredes, Roberto; Garcia-Franco, Enrique; Cabello, Juan Pous; Ortega, Marcelo F. (Applied sciences, 2025)
The integration of renewable energy with circular economy strategies offers effective pathways to reduce greenhouse gas emissions while enhancing local energy independence. This study analyses three real-world projects implemented in Spain that exemplify this synergy. LIFE Smart Agromobility converts pig manure into biomethane to power farm vehicles, using anaerobic digestion and microalgae-based upgrading systems. Smart Met Value refines biogas from a wastewater treatment plant in Guadalajara to produce high-purity biomethane for the municipal fleet, demonstrating the viability of energy recovery from sewage sludge. The UNDERGY project addresses green hydrogen storage by repurposing a depleted natural gas reservoir, showing geochemical and geomechanical feasibility for seasonal underground hydrogen storage. Each project utilises regionally available resources to produce clean fuels—biomethane or hydrogen—while mitigating methane and CO2 emissions. Results show significant energy recovery potential: biomethane production can replace a substantial portion of fossil fuel use in rural and urban settings, while hydrogen storage provides a scalable solution for surplus renewable energy. These applied cases demonstrate not only the technical feasibility but also the socio-economic benefits of integrating waste valorisation and energy transition technologies. Together, they represent replicable models for sustainable development and energy resilience across Europe and beyond.